Pleasantness shapes congruency effects in odor-induced taste enhancement - Ao Wang; Xinyi Wu; Lin Gao; Qingya Yang; Liuqing Wei; Lingkai Ji; Simin Zhao; Weiping Yang; Mengling Chen; Pei Liang (Food Quality and Preference, 2026)

Correction: Effect of lycium barbarum polysaccharide on ameliorating high-fat diet-damaged spermatogenesis via PCSK9 and TLR4 signaling pathways in obese mice - Jinyuan Wang; Yuru Chen; Rongqian Ni; Mingxuan Su; Yichang Cao; Runtang Zhou; Xiang Li; Jiangming Li; Yuxia Tang; Jiayi Tang; Simin Wang; Linyue Tang; et al. (Molecular Biology Reports, 2026)

Coupled orbital and ENSO forcing shaped the Holocene evolution of East Asian precipitation patterns - Anguo Xiao; Yanzhen Li; Teng Liu; Ze Zhang; Simin Jin; Ruiyao Zhang; Xiaosong Chen; Chunju Huang (Quaternary Science Reviews, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Bioaerosols in the atmospheric environment of oil exploitation sites: spatial and temporal distribution, sources, influencing factors, health risks, and reduction efficiency of masks - Hongjie Yang; Shen He; Zongting Yao; Hao Li; Qihao Feng; Simin Huang; Zhen Chen; Jiasheng Ni; Zhishu Liang (Environmental Pollution, 2026)

A sulfonate-rich gel electrolyte enables coupled polyiodide confinement and Zn2+ transport regulation for durable aqueous ZnI2 batteries - Qing Luo; Ling Wang; Simin Chai; Yuwei Li; Xin Lin; Jinpeng Guan; Zetao Chen; Caifeng Li; Na Li; Lin Zeng; Jianxiong Xu (Chemical Engineering Journal, 2026)

Low-dose sodium acetate-mediated energy compensation stabilizes oxygen-limited urea hydrolysis coupled with partial nitritation/anammox for high-strength urea wastewater treatment - Meng Yang; Yonggan Li; Yongxing Chen; Yu Zhang; Yasong Wang; Qingyu Liu; Simin Lu; Xiaojun Wang (Bioresource Technology, 2026)

Effects of igneous erosion on the microstructure and spontaneous combustion characteristics of coals - Leilin Zhang; Simin Chen; Xiumin Xie (Fuel, 2026)

The patterns and driving forces of orbital-to millennial-timescales East Asian summer monsoon precipitation variations during the last glaciation - Yi Li; Jingwei Zhang; Xinmiao Chen; Zhi Zhang; Qingfeng Shao; Xinggong Kong; Simin Peng (CATENA, 2026)

HtpsB, a type II histidine triad protein of Streptococcus suis, contributes to bacterial virulence and blood-brain barrier disruption - Jingyan Fan; Jinpeng Zhang; Baiyi Chen; Yixin Han; Hexiang Jiang; Simin Deng; Luqing Cui; Xiaolu Lai; Kalliopi Rantsiou; Luca Simone Cocolin; Rui Zhou; Houhui Song; et al. (Veterinary Microbiology, 2026)

The transcription factor SbWRKY6 confers cadmium tolerance via activating SbPLAC8–17 expression in sorghum - Shan Cao; Jiqing Zhang; Zhengyu Guo; He Wang; Zengting Chen; Simin Li; Na Sui (Journal of Hazardous Materials, 2026)

Corrigendum to “Multimodal luminescence of CaZnGe2O6:Mn2+,Yb3+ phosphors for anti-counterfeiting: dynamic photoluminescence, afterglow, photostimulated luminescence, thermostimulated luminescence and mechanoluminescence” [Chem. Eng. J. 524 (2025) 169152] - Simin Yu; Yujia Gong; Guanlin He; Anfei Chen; Qiaoling Chen; Changkui Duan; Hai Guo (Chemical Engineering Journal, 2026)

Paratenon mimetic multifunctional bifacial hydrogel for postoperative Achilles tendon remodeling - Bo Zhang; Qingrui Fan; Fangxue Zhang; Zhen Zhang; Simin Kong; Menghan Chien; Rao Chen; Jiying Zhang; Mingze Du; Liya Ai; Jianjun Wang; Dong Jiang (Chemical Engineering Journal, 2026)

Deep removal of aqueous arsenic by thermally activated and Fe-impregnated steel slag: Mechanism and dynamic column experiments - Shuang Chen; Simin Xiong; Zhanfang Cao; Guangyi Liu (Journal of Water Process Engineering, 2026)

Low-temperature semi-solid-state H2 battery with high energy density - Xiuquan Chen; Yuhua Zhao; Simin Hong; Xiaodong Rang; Hong Dong; Jie Zhang; Shangjun Lu; Xiang Cui; Yajing Liu (Chemical Engineering Journal, 2026)

Distributed three-dimensional target enclosing control for AUVs under ocean currents - Linlin Shi; Haoming Wu; Biao Wei; Simin Lv; Yang Xu; Ronghao Zheng; Yu Chen (Ocean Engineering, 2026)

Facile calcium-iron materials for economical removal of As(Ⅲ) and As(Ⅴ): Preparation, mechanism and granulation application - Shuang Chen; Simin Xiong; Wei Chen; Guangyi Liu (Journal of Environmental Chemical Engineering, 2026)

A Study on the Mountainous Merging Precipitation Model and Effective Covariates - Mengya Xing; Simin Qu; Peng Jiang; Xing Chen; Wen Ji (Water Resources Management, 2026)

Lactobacillus plantarum ameliorates intrahepatic cholestasis by modulating the gut microbiota and tryptophan metabolism - Shijing Dong; Liping Guo; Chenyang Xuan; Chenhui Zhu; Zongze Han; Nian Chen; Xinyu Wang; Meng Shen; Xiaoxuan Wei; Hui Yang; Xue Zhang; Man Liu; et al. (Food Research International, 2026)

Key enzymes in N6-methyladenosine modification regulate plant stress tolerance by modulating mRNA stability - Zishuo Han; Hongxiang Zheng; Yinping Gao; Simin Li; Zengting Chen; Fangning Zhang; Fenghui Wu; Zhiying Zhao; Lei Yan; Na Sui (Plant Cell Reports, 2026)

High performance portable sensor based on excellent conductive composite MXene@Ag-MEL for detection of gallic acid in foods - Xingxing Zeng; Dongnan Zhang; Simin Chen; Xiaozi Huang; Zhenxia Zhao; Xin Li; Baoyu Liu (Food Chemistry, 2026)

Simultaneous nitrogen and fluoride removal from photovoltaic wastewater via a microalgal-bacterial consortia: Performance and fluorapatite biomineralization - Simin Liao; Ling Lai; Zhensheng Xiong; Suhua Chen; Gengxin Zhou; Chenghang Tu; Wei Ren; Liming Yang; Xubiao Luo (Chemical Engineering Journal, 2026)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury after SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2026)

Convallatoxin ameliorates fibroblast-like synoviocytes-mediated synovial inflammation and joint destruction in rheumatoid arthritis by targeting IDH1 - Suling Liu; Huijuan Hu; Yu Kuang; Simin Chen; Kai Sun; Chenxi Peng; Ruiru Li; Fan Su; Liuqin Liang; Qian Qiu; Youjun Xiao; Hanshi Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Highly effective masculinization of mandarin fish (Siniperca chuatsi) using Etonogestrel: A practical method for aquaculture and transcriptomic mechanism elucidation - Jiangwei Zhou; Simin Zhong; Shengyue Lin; Shuzheng Ye; Dingxian Chen; Chong Han; Qiang Li (Aquaculture, 2026)

Enhancing taste without salt or sugar: Cross-modal flavor modulation via olfactory cues - Ao Wang; Xinyi Wu; Lin Gao; Qingya Yang; Liuqing Wei; Lingkai Ji; Simin Zhao; Weiping Yang; Mengling Chen; Pei Liang (Food Quality and Preference, 2026)

AI-assisted discovery of dual antioxidant and ACE-inhibitory peptides from Hericium erinaceus - Rongheng Chen; Jiahao Yu; Simin Feng; Ping Shao (Food Chemistry, 2026)

The ultra-large-capacity silica-supported ferric oxyhydroxide material: Preparation and mechanism on arsenic removal from water - Shuang Chen; Simin Xiong; Wei Chen; Guangyi Liu (Environmental Research, 2026)

Efficacy and safety of vunakizumab between super responders and non-super responders of patients with moderate-to-severe plaque psoriasis: a post-hoc exploratory analysis of a phase III trial - Ougen Liu; Caixia Kou; Simin Yu; Huizhong Hu; Xiaoxiao Chen; Meiying Jiang; Shifeng Ren (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Identification of porcine-derived atypical intestinal pathogenic Escherichia coli reveals to a hidden threat of extraintestinal infection - Zhonghao Chen; Simin Lv; Shiyu Zhang; Yong Yu; Jiale Ma; Huochun Yao; Xinming Pan (Veterinary Microbiology, 2026)

Melatonin alleviates cholestatic liver injury through modulating gut microbiota and activating the NRF2/HO-1 antioxidant pathway - Shijing Dong; Jiangpeng Liu; Chenyang Xuan; Simin Zhou; Zongze Han; Chenhui Zhu; Nian Chen; Ruiyun Liu; Weirong Wang; Hongyu Chu; Xue Zhang; Hui Yang; et al. (Tissue and Cell, 2026)

Engineered asymmetric biomimetic skin patch with dynamic biointeractivity via microphase separation for enhanced wound regeneration - Dongmei Zhang; Simin Chen; Yihui Liu; Zixin Wang; Jiayi Wang; Shilian Zheng; Zijia Zhang; Qianjie Zhang; Wanpin Zhang (Chemical Engineering Journal, 2026)

Enhanced recovery of rare earth elements from mine wastewater using microbial-derived ferrous sulfide - Simin Jiang; Ronghao Wu; Qu Zhang; Zuliang Chen (Water Research, 2026)

Dynamic development of global contiguous flash droughts: from an event-based spatiotemporal perspective - Dingkui Wang; Xuezhi Tan; Xinxin Wu; Zeqin Huang; Simin Deng; Yaxin Liu; Jianyu Fu; Xuejin Tan; Xitian Cai; Bingjun Liu; Haiyun Shi; Long Yang; et al. (Journal of Hydrology, 2025)

Improved water solubility of myofibrillar protein through enzymatic deamidation and glycosylation: Insights into molecular behavior of myosin - Miao Feng; Yuxin Huang; Xuefei Wang; Simin Zheng; Qian Chen; Baohua Kong; Haotian Liu; Chao Zhang (Food Chemistry, 2025)

Potassium and phosphorus co-doped g-C3N4 with improved carrier migration for efficient photocatalytic degradation of 2,4-dichlorophenoxyacetic acid under visible light - Shan Liu; Simin Long; Yi Zhao; Zhonglin Chen; Jimin Shen; Gang Fu; Jiaxu Zhang; Jing Kang (Environmental Research, 2025)

Effect of lycium barbarum polysaccharide on ameliorating high-fat diet-damaged spermatogenesis via PCSK9 and TLR4 signaling pathways in obese mice - Jinyuan Wang; Yuru Chen; Rongqian Ni; Mingxuan Su; Yichang Cao; Runtang Zhou; Xiang Li; Jiangming Li; Yuxia Tang; Jiayi Tang; Simin Wang; Linyue Tang; et al. (Molecular Biology Reports, 2025)

Study on the effects of phosphoric acid-modified biochar on the adsorption behavior and bioavailability of oxytetracycline in saline-alkali soils - Runfang Yao; Shiqi Tao; Yuyun Chen; Zengyu Liu; Simin Feng (Environmental Geochemistry and Health, 2025)

Oxidative stress and ferroptosis in diabetic cardiomyopathy: mechanistic interplay and therapeutic implications - Shan Li; Yuhe Shu; Shuyu Yang; Simin Zhang; Haoling Chen; Dan Wu; Bo Li; Li Dong (Apoptosis, 2025)

Activation of the cGAS-STING pathway in monocytes exacerbates pulmonary fibrosis induced by paraquat poisoning - Yangyang Sun; Zheming Yuan; Weidong Li; Xueyang Lin; Chen Yang; Yufeng Yang; Hui Miao; Shengran Wang; Ziqi Cui; Zhenghao Bao; Simin Lang; Weiqiang Sun; et al. (Toxicology and Applied Pharmacology, 2025)

Multimodal luminescence of CaZnGe2O6:Mn2+,Yb3+ phosphors for anti-counterfeiting: dynamic photoluminescence, afterglow, photostimulated luminescence, thermostimulated luminescence and mechanoluminescence - Simin Yu; Yujia Gong; Guanlin He; Anfei Chen; Qiaoling Chen; Changkui Duan; Hai Guo (Chemical Engineering Journal, 2025)

Mendelian randomization analysis reveals causal associations between autoimmune diseases and female infertility risk - Jinyuan Wang; Haojun Long; Mingxuan Su; Yichang Cao; Runtang Zhou; Xiang Li; Jiangming Li; Yuxia Tang; Jiayi Tang; Simin Wang; Linyue Tang; Ruxin Chen; et al. (Reproductive Toxicology, 2025)

Integrated non-target screening and temporal trend analysis of emerging contaminants: Implications for drinking water source management from a wet and dry season perspective - Qiu Li; Zhenguo Chen; Xiaojun Liang; Simin Lu; Xiaojun Wang (Journal of Environmental Chemical Engineering, 2025)

Novel receptor-binding protein from phage PJNS004 for sensitive detection of Salmonella - Yibao Chen; Simin Yang; Qing Zhang; Ming Hu; Qianghua Lv; Xiaonan Zhao; Lulu Li; Yanbo Luo; Xiaohui Xu; Yujun Zhao; Yuqing Liu (Food Chemistry, 2025)

Effect of dry heat treatment temperature of skim milk powder on the improved heat stability of recombined filled evaporated milk - Zijun Zhao; Simin Chen; Bruno De Meulenaer; Jianfeng Wu; Paul Van der Meeren (Food Hydrocolloids, 2025)

Nitrogen and phosphorus preferring photogranules regulate COD/TN by carbon fixation through superposition of Chlorophyta, Cyanobacteria and Chloroflexi - Chenghang Tu; Zhensheng Xiong; Mengsha Dai; Simin Liao; Li Xie; Binghong Chen; Helen Yu (Chemical Engineering Journal, 2025)

Human gut Bifidobacterium longum subsp. suillum is enriched in vitro by a pectic polysaccharide isolated from the flowers of Lilium lancifolium - Meixia Li; Renjie Liu; Tao Wang; Lana Duo; Guo Chen; Mengfei Mao; Yue Sun; Yun Li; Simin Cai; Wanqi Zhou; Haibiao Lai; Kan Ding (Carbohydrate Polymers, 2025)

Protective effects of berberine on MASLD: regulation of glucose and lipid metabolism through PI3K/Akt and STING pathways - Jing Ji; Ying Li; Tian Xu; Qi Shao; Zijin Sun; Simin Chen; Di Zhang; Qingguo Wang; Xueqian Wang; Chongyang Ma; Fafeng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Enhanced extraction of microplastics from terrestrial animal intestinal tissues via optimized fenton oxidation - Simin Yu; Jiaqi Chen; Zhanao Zhang; Yanping Zhao; Yan Zhang (Journal of Hazardous Materials, 2025)

Mechanistic insights into the selective recovery of rare earth elements from mine wastewater using green-synthesized silver nanoparticles - Simin Jiang; Xinmiao Xu; Wei Chen; Zuliang Chen (Environmental Research, 2025)

Studies on the effect of microplastics on the adsorption and migration of Phenanthrene in river sediment - Simin Feng; Runfang Yao; ·Yuyun Chen; Hongli Zhang (Environmental Geochemistry and Health, 2025)

Prospects and limitations of NK cell adoptive therapy in clinical applications - Yamin Deng; Chen Wu; Jintong Na; Jing Tang; Simin Qin; Zhiyong Zhang; Liping Zhong (Cancer and Metastasis Reviews, 2025)

Simple synthesis and excellent performance of the cow dung–based biodegradable liquid mulch for sustainable agriculture - Xiaohao Guo; Yuankai Zhou; Simin Li; Zhiwen Li; Wei Liu; Yalan Zhang; Hu Du; Wenrong Xiong; Qi Li; Yanyan Zhong; Tian Qin; Mengting Wu; et al. (Environmental Research, 2025)

The Impact of Microplastics on Adsorption of Chlorophenols by River-Suspended Sediments - Shiqi Tao; Simin Feng; Yuyun Chen; Ting Duan; Zengyu Liu; Ling Li; Rongrong Yun; Chayma Chilouch (Environmental Management, 2025)

Selective recovery of rare earth elements from mine wastewater using the magnetic zeolite prepared by rare earth tailings - Jianhui Zhang; Jianchen Cheng; Guizhou Xu; Xuechao Hou; Zhifei Yu; Wei Liu; Yalan Zhang; Jianxin Chen; Jiahao Yang; Mengting Wu; Wanqing Yang; Simin Li; et al. (Chemical Engineering Journal, 2025)

Combined toxicity evaluation of polystyrene nanoplastics and Nano-ZnO of distinctive morphology on human lung epithelial cells - Henghui Li; Simin Tang; Xiaoyu Jia; Xinyi Zhu; Ling Cai; Mingxiu Duan; Shaozhuo Wang; Huijun Jiang; MingHui Ji; Shoulin Wang; Jin Chen (Science of The Total Environment, 2025)

Arsenic removal by thermally activated limonite: Adsorption performance and mechanism - Simin Xiong; Shuang Chen; Wei Chen; Wenbin Xia; Guangyi Liu (Journal of Water Process Engineering, 2025)

Correction to: Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)

Inhibition of USP30 Promotes Mitophagy by Regulating Ubiquitination of MFN2 by Parkin to Attenuate Early Brain Injury After SAH - Yang Liu; Chenbei Yao; Bin Sheng; Simin Zhi; Xiangxin Chen; Pengfei Ding; Jiatong Zhang; Zhennan Tao; Wei Li; Zong Zhuang; Jiannan Mao; Zheng Peng; et al. (Translational Stroke Research, 2025)
Subarachnoid hemorrhage (SAH) is a type of stroke with a high disability and mortality rate. Apoptosis caused by massive damage to mitochondria in neuron cells and inflammatory responses caused by high extracellular ATP lead to poor outcomes. USP30 is a deubiquitinating enzyme that inhibits mitophagy, resulting in a failure to remove damaged mitochondria in a timely manner after SAH; nevertheless, the pathway through which USP30 inhibits mitophagy is unknown. This study evaluated the neuroprotective role and possible molecular basis by which inhibiting USP30 to attenuate SAH-induced EBI by promoting neuronal mitophagy. We used an in vitro model of hemoglobin exposure and an in vivo model of intravascular perforation. Increased expression of USP30 was found after SAH in vivo and in vitro, and USP30 inhibition expression in SAH mice treated with MF094 resulted in significant improvement of neurological injury and inflammatory response and mediated good outcomes, suggesting a neuroprotective effect of USP30 inhibition. In cultured neurons, inhibition of USP30 promoted ubiquitination modification of mitochondrial fusion protein 2 (MFN2) by E3 ubiquitin ligase (Parkin), separating damaged mitochondria from the healthy mitochondrial network and prompting mitophagy, causing early clearance of damaged intracellular mitochondria, and reducing the onset of apoptosis. The high extracellular ATP environment was meliorated, reversing the conversion of microglia to a pro-inflammatory phenotype and reducing inflammatory injury. USP30 inhibition had no autophagy-promoting effect on structurally and functionally sound mitochondria and did not inhibit normal intracellular ATP production. The findings suggest that USP30 inhibition has a neuroprotective effect after SAH by promoting early mitophagy after SAH to clear damaged mitochondria.

Understanding the Antidepressant Mechanisms of Acupuncture: Targeting Hippocampal Neuroinflammation, Oxidative Stress, Neuroplasticity, and Apoptosis in CUMS Rats - Jianguo Li; Xinhong Wu; Simin Yan; Junliang Shen; Tao Tong; Muhammad Shahzad Aslam; Jingyu Zeng; Yiping Chen; Wenjie Chen; Meng Li; Zhuoran You; Kaiyue Gong; et al. (Molecular Neurobiology, 2025)

Structure of myelin in the central nervous system and another possible driving force for its formation—myelin compaction - Qi Shao; Simin Chen; Tian Xu; Yuyu Shi; Zijin Sun; Qingguo Wang; Xueqian Wang; Fafeng Cheng (Journal of Zhejiang University-SCIENCE B, 2025)

Household waste-specific ambient air shows greater inhalable antimicrobial resistance risks in densely populated communities - Zhipeng Zheng; Wenhui Ji; Xiao Wang; Xueting Wang; Simin Dai; Zhaowen Zhang; Yinghua Zhang; Xiaoyan Wang; Shen Cao; Min Chen; Bing Xie; Jun Feng; et al. (Waste Management, 2025)

One-step construction of FeP/carbon aerogel composites and their efficient tetracycline removal mechanisms: Adsorption, in situ oxygen activation and electron transfer - Guilong Wang; Rongyuan Jiang; Juntao Chen; Simin Li; Guanfeng Lin; Beili Lu; Biao Huang; Jianwei Zhao; Lei Yang (Journal of Water Process Engineering, 2025)

Mercury deposition in central China from the Last Glacial Maximum to the early Holocene recorded in an accurately-dated stalagmite - Yanzhen Li; Liangcheng Tan; Simin Jin; Hai Xu; Lüfan Chen; David B. Kemp; Ashish Sinha; Le Ma; Chunju Huang; Lawrence R. Edwards; Hai Cheng (Science Bulletin, 2025)

Removal of heavy metals from water by adsorption on metal organic frameworks: Research progress and mechanistic analysis in the last decade - Fang Yuan; Dingfan Yan; Shuaibo Song; Jinbo Zhang; Yangyang Yang; Zheng Chen; Jiahao Lu; Simin Wang; Yongjun Sun (Chemical Engineering Journal, 2025)

Concentration, pathogenic composition, and exposure risks of bioaerosol in large indoor public environments: A comparative study of urban and suburban areas - Jiasheng Ni; Simin Huang; Zhishu Liang; Zhen Chen; Simeng Zhang; Guiying Li; Taicheng An (Science of The Total Environment, 2024)

Carboxymethyl chitosan/polyvinyl alcohol hydrogel films by incorporating MSNs as ε-PL carrier with pH-responsive controlled release and antibacterial properties - Debao Wang; Simin Fan; Xin Li; Li Chen; Xiangyuan Wen; Yuqian Xu; Chaoqiao Zhu; Chengli Hou; Dequan Zhang (Food Packaging and Shelf Life, 2024)

The role of ApoE in fatty acid transport from neurons to astrocytes under ischemia/hypoxia conditions - Hongyan Chen; Shaozhi Zhao; Qiang Jian; Yinfang Yan; Simin Wang; Xinwen Zhang; Yuqiang Ji (Molecular Biology Reports, 2024)

Mobilization of phosphorus in sediments of eutrophic lakes induced by elevated sulfate levels - Lanqing Zhang; Miaotong Yu; Simin Yu; Huaizhi Chen; Mengmeng Xiao; Guoxiang Wang; Yanping Zhao (Science of The Total Environment, 2024)

Global hydroclimate perturbations during the Toarcian oceanic anoxic event - David B. Kemp; Zhong Han; Xiumian Hu; Wenhan Chen; Simin Jin; Kentaro Izumi; Qing Yan; Viktória Baranyi; Xin Jin; Jacopo Dal Corso; Yuzhu Ge (Earth-Science Reviews, 2024)

Formation of flake-like DAAF crystals with tunable size realized on a microfluidic platform for binder-free initiator explosives - Bo Yang; Shengshu Xi; Simin He; Jin Chen; Wei Cao; Rui Li; Rupeng Bu; Xiaona Huang; Jincan Zhu; Qi Wu; Weimiao Wang; Xiaodong Li; et al. (Chemical Engineering Journal, 2024)

A bifunctional amylopullulanase of Streptococcus suis ApuA contributes to immune evasion by interaction with host complement C3b - Jiajia Xu; Jiaqi Zhu; Weiyao Han; Siqi Pang; Simin Deng; Long Chen; Xiabing Chen; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2024)

Ambient ultrafine particles exacerbate oxygen desaturation during sleep in patients with chronic obstructive pulmonary disease: New insights into the effect spectrum of ultrafine particles on susceptible populations - Wenlou Zhang; Baiqi Chen; Yoshiko Yoda; Masayuki Shima; Chen Zhao; Xuezhao Ji; Junyi Wang; Sha Liao; Simin Jiang; Luyi Li; Yahong Chen; Xinbiao Guo; et al. (Science of The Total Environment, 2024)

Associations of occupational exposure to micro-LiNiCoMnO2 particles with systemic inflammation and cardiac dysfunction in cathode material production for lithium batteries - Yaotang Deng; Guoliang Li; Lijie Xie; Xiaoliang Li; Youyi Wu; Jiewei Zheng; Simin Xian; Jiazhen Zhou; Jiabin Chen; Yuewei Liu; Qiaoyuan Yang; Qing Wang; et al. (Environmental Pollution, 2024)

Self-assembled Chitosan/Polyvinyl alcohol hydrogel film incorporated with TiO2 with excellent stability, mechanical and antibacterial properties for the preservation of chilled pork - Debao Wang; Juan Chen; Xiangyuan Wen; Simin Fan; Chaoqiao Zhu; Xin Li; Fei Fang; Wei Yang; Wenchun Fan; Dequan Zhang; Chengli Hou (Food Packaging and Shelf Life, 2024)

Separable Janus photothermal PPy@PVA-PVDF/F-SiO2-PVDF bilayer membrane for low-cost, efficient and sustainable solar-driven membrane desalination in oil-contaminated seawater - Zhaochuan Chen; Xin Meng; Chenlu Qian; Simin Huang; Xuemei Chen (Chemical Engineering Journal, 2024)

Pediococcus pentosaceus MIANGUAN Enhances the Immune Response to Vaccination in Mice - Yulu Chen; Zhijie Cao; Simin Lu; Zhihuan Wang; Caiyun Ma; Gui Zhang; Mengshan Chen; Jing Yang; Zhihong Ren; Jianguo Xu (Probiotics and Antimicrobial Proteins, 2024)

A DNA walker based on hairpin-shaped DNA aligner and fueled by nicking endonuclease for sensitive and rapid miRNA analysis - Ting Huang; Zhenbang Lu; Peixian Mo; Piao Liu; Simin Liu; Jing Peng; Rongtian Li; Nuan Jia; Minmin Li; Zong Dai; Jun Chen; Jinxiang Chen (Analytica Chimica Acta, 2024)

How does the biochar-supported sulfidized nanoscale zero-valent iron affect the soil environment and microorganisms while remediating cadmium contaminated paddy soil? - Wenjing Xue; Siqi Wen; Xinyu Chen; Yu Wang; Simin Qian; Yiyun Wu; Rongrong Ge; Yang Gao; Yiqun Xu (Environmental Geochemistry and Health, 2024)

Response mechanism of a highly efficient partial nitritation-anammox (PN/A) process under antibiotic stress: Extracellular polymers, microbial community, and functional genes - Yingqiang Li; Zhenguo Chen; Yuexiang Huang; Chunying Zheng; Simin Lu; Xinzhi Wang; Chao Zhang; Xiaohui Yi; Mingzhi Huang (Environmental Research, 2024)

H2S is involved in drought-mediated stomatal closure through PLDα1 in Arabidopsis - Simin Wang; Cuixia Zhang; Rongshan Chen; Kailin Cheng; Liai Ma; Wei Wang; Ning Yang (Planta, 2024)

Potential retention of dissolved organic matter by soil minerals during wetland water-table fluctuations - Simin Wang; Ting Liu; Erxiong Zhu; Chen He; Quan Shi; Xiaojuan Feng (Water Research, 2024)

Effects of Lipid on the Formation of Heterocyclic Aromatic Amines and Advanced Glycation End Products in Thermally Processed Fish - Xi Chen; Ruichun Wang; Haixia Yu; Yingying Huang; Simin Zhang (Journal of Aquatic Food Product Technology, 2024)

Natural aging and adsorption/desorption behaviors of polyethylene mulch films: Roles of film types and exposure patterns - Jingcheng Liang; Xian Chen; Xiaotong Duan; Xueyuan Gu; Xiaopeng Zhao; Simin Zha; Xingming Chen (Journal of Hazardous Materials, 2024)

A nested case-control study of serum zinc and incident diabetes among Chinese adults: Effect modifications and mediation analysis - Jingli Yang; Zhiyuan Cheng; Desheng Zhang; Tongzhang Zheng; Chun Yin; Simin Liu; Lizhen Zhang; Zhongge Wang; Yufeng Wang; Ruirui Chen; Qian Dou; Yana Bai (Science of The Total Environment, 2024)

Obscuring effect of income inequality and moderating role of financial literacy in the relationship between digital finance and China's household carbon emissions - Simin Huang; Lin Yang; Chen Yang; Donghan Wang; Yiming Li (Journal of Environmental Management, 2024)

Iron-based materials for activation of periodate in water and wastewater treatment processes: The important role of Fe species - Huiping Zeng; Yong Chen; Jiaxin Xu; Simin Li; Jiahao Wu; Dong Li; Jie Zhang (Chemical Engineering Journal, 2024)

Alleviative effects of mannosylerythritol lipid-A on the deterioration of internal structure and quality in frozen dough and corresponding steamed bread - Siyu Liu; Simin Gu; Ying Shi; Qihe Chen (Food Chemistry, 2024)

Golgi-triggered radiation sensitizer retention enhances the efferocytosis and immunotherapy in breast cancer with skeleton metastases - Yi-chuan Pang; Xiaotong Qiu; Simin Liu; Yanlei Huo; Xiaoli Yang; Chao Ma; Min qi; Xiaojun Chen; Zhi-hang Zhou; Zhongwei Lv (Chemical Engineering Journal, 2024)

An Adaptive Conjugate Gradient Least-Squares Regularization (ACGLSR) Method for 3D Gravity Density Inversion - Wenjin Chen; Robert Tenzer; Xiaolong Tan; Simin Zhao (Pure and Applied Geophysics, 2024)

Pectoral muscle removal in mammogram images: A novel approach for improved accuracy and efficiency - Simin Chen; Debbie L. Bennett; Graham A. Colditz; Shu Jiang (Cancer Causes & Control, 2024)
Purpose Accurate pectoral muscle removal is critical in mammographic breast density estimation and many other computer-aided algorithms. We propose a novel approach to remove pectoral muscles form mediolateral oblique (MLO) view mammograms and compare accuracy and computational efficiency with existing method (Libra). Methods A pectoral muscle identification pipeline was developed. The image is first binarized to enhance contrast and then the Canny algorithm was applied for edge detection. Robust interpolation is used to smooth out the pectoral muscle region. Accuracy and computational speed of pectoral muscle identification was assessed using 951 women (1,902 MLO mammograms) from the Joanne Knight Breast Health Cohort at Washington University School of Medicine. Results Our proposed algorithm exhibits lower mean error of 12.22% in comparison to Libra’s estimated error of 20.44%. This 40% gain in accuracy was statistically significant ( p < 0.001). The computational time for the proposed algorithm is 5.4 times faster when compared to Libra (5.1 s for proposed vs. 27.7 s for Libra per mammogram). Conclusion We present a novel approach for pectoral muscle removal in mammogram images that demonstrates significant improvement in accuracy and efficiency compared to existing method. Our findings have important implications for the development of computer-aided systems and other automated tools in this field.

Comparative miRNA-seq analysis revealed molecular mechanisms of red color formation in the early developmental stages of Plectropomus leopardus - Xi Liu; Mouyan Jiang; Simin Wen; Kaixiang Zhang; Yucong Hong; Kaihui Sun; Xianwu Deng; Yang Huang; Gang Shi; Changxu Tian; Huapu Chen; Guangli Li; et al. (Frontiers in Marine Science, 2023)
MicroRNAs (miRNAs) are endogenous small non-coding RNAs that play important roles in several biological processes, including the regulation of body color. Leopard coral grouper ( Plectropomus leopardus ) is a valuable marine aquaculture fish; however, at present, there are no published reports on its early body color development. The skin color of P. leopardus undergoes a transition from transparent to red from 26 days post-hatching (dph) to 30 dph. In this study, we performed miRNA sequencing on 26 dph (Transparent, PT) and 30 dph (Red, PR) skin samples of P. leopardus to explore the molecular mechanism underlying red color formation. A total of 44.31 M and 37.55 M clean tags were obtained from PT and PR group, respectively. Among these tags, 981 miRNAs were identified, including 493 known and 488 novel miRNAs. A total of 106 differentially expressed miRNAs (DEMs) were identified in PT vs. PR, with 43 up-regulated and 63 down-regulated miRNAs in the PR group, compared to the PT group (|fold change| > 2 and p-value < 0.05). A miRNA-mRNA network based on 18 candidate miRNAs and 53 target genes related to pigmentation, and KEGG enrichment analysis of the target genes of all DEMs, revealed that miRNAs involved in the formation of red skin color were mainly related to: 1) the inhibition of melanin synthesis (miR-141-z, miR-206-z, miR-206-y, miR-27-z, miR-137-y, miR-204-x, miR-204-y, miR-211-x, miR-211-z); 2) chromatophore development (miR-206-z, miR-206-y, miR-499-y, miR-1-z, miR-2188-x, miR-423-x); and 3) carotenoid metabolism (miR-204-x, miR-204-y, miR-499-y). This study demonstrates the potential role of miRNAs in red color formation and lays the foundation for the molecular mechanism of body color polymorphism in P. leopardus .

Altered functional brain networks in coronary heart disease: independent component analysis and graph theoretical analysis - Simin Lin; Puyeh Wu; Shaoyin Duan; Qianni Du; Shujia Guo; Zhishang Chen; Naiming Wu; Xiaoyan Chen; Ting Xie; Yi Han; Hengyu Zhao (Brain Structure and Function, 2023)

Environmental, social, and governance (ESG) performance and financial outcomes: Analyzing the impact of ESG on financial performance - Simin Chen; Yu Song; Peng Gao (Journal of Environmental Management, 2023)

Free nitrous acid prediction in ANAMMOX process using hybrid deep neural network model - Junlang Li; Jilan Dong; Zhenguo Chen; Xiaoyong Li; Xiaohui Yi; Guoqiang Niu; Jiaan He; Simin Lu; Yuxiang Ke; Mingzhi Huang (Journal of Environmental Management, 2023)

Identification of the MYB gene family in Sorghum bicolor and functional analysis of SbMYBAS1 in response to salt stress - Mei Lu; Zengting Chen; Yingying Dang; Jinlu Li; Jingyi Wang; Hongxiang Zheng; Simin Li; Xuemei Wang; Xihua Du; Na Sui (Plant Molecular Biology, 2023)

Selective and efficient removal of lanthanum ion in aqueous solution by P-doped porous carbon - Guanfeng Lin; Yongzhi Xiong; Guilong Wang; Simin Li; Rongyuan Jiang; Beili Lu; Yandan Chen; Biao Huang (Journal of Water Process Engineering, 2023)

Applicability assessment of five evapotranspiration models based on lysimeter data from a bioretention system - Wenlong Zhang; Moyuan Yang; Shouhong Zhang; Lei Yu; Fei Zhao; Duwei Chen; Simin Yang; Hualin Li; Sunxun Zhang; Ruixian Li; Jianjun Zhang (Ecological Engineering, 2023)

Enantioselective effects of paclobutrazol and its enantiomers on glycolipid metabolism in zebrafish (Danio rerio) - Dong Guo; Simin Chen; Weiguang Zhang; Jun Fan (Pesticide Biochemistry and Physiology, 2023)

Protein interactions during dry and wet heat pre-treatment of skim milk powder (dispersions) and their effect on the heat stability of recombined filled evaporated milk - Jianfeng Wu; Simin Chen; Els J.M. Van Damme; Bruno De Meulenaer; Paul Van der Meeren (Food Chemistry, 2023)

Response of PM2.5 pollution to meteorological and anthropogenic emissions changes during COVID-19 lockdown in Hunan Province based on WRF-Chem model - Simin Dai; Xuwu Chen; Jie Liang; Xin Li; Shuai Li; Gaojie Chen; Zuo Chen; Juan Bin; Yifan Tang; Xiaodong Li (Environmental Pollution, 2023)

Distribution and Characteristics of Microplastics in Agricultural Soils around Gehu Lake, China - Jingcheng Liang; Xian Chen; Simin Zha; Xingming Chen; Yijun Yu; Xiaotong Duan; Yiran Cao; Yuechang Liang (Water, Air, & Soil Pollution, 2023)

Association of multiple air pollutants with oxygen saturation during sleep in COPD patients: Effect modification by smoking status and airway inflammatory phenotypes - Wenlou Zhang; Junyi Wang; Baiqi Chen; Xuezhao Ji; Chen Zhao; Maike Chen; Sha Liao; Simin Jiang; Zihan Pan; Wanzhou Wang; Luyi Li; Yahong Chen; et al. (Journal of Hazardous Materials, 2023)

Impact of three phycospheric bacterial strains on the growth and fatty acid composition of Isochrysis galbana - Minnan Wu; Jiayi Cao; Yijun Xu; Simin Xu; Zhengbo Zhou; Mengmeng Shao; Ziyue Wang; Lin Zhang; Deshui Chen; Yuanyuan Wu; Jilin Xu; Xiaojun Yan (Algal Research, 2023)

Enhancing the Thermotolerance of Isochrysis zhangjiangensis Through Co-culturing With Algoriphagus marincola - Simin Xu; Jiayi Cao; Minnan Wu; Yijun Xu; Yuanyuan Wu; Kaixi Shang; Bin Ma; Lin Zhang; Deshui Chen; Xinyu Liu; Xiaojun Yan; Jilin Xu (Marine Biotechnology, 2023)

Design, synthesis and mechanism study of novel natural-derived isoquinoline derivatives as antifungal agents - Wei Chen; Rui Zhang; Yang Chen; Pingbing Yu; Yuxin Lan; Haojian Xu; Simin Lei (Molecular Diversity, 2023)

Plasma Metabolic Analysis Reveals the Dysregulation of Short-Chain Fatty Acid Metabolism in Parkinson’s Disease - Ao Qi; Lulu Liu; Junjie Zhang; Simei Chen; Simin Xu; Yusen Chen; Lijiang Zhang; Chun Cai (Molecular Neurobiology, 2023)

Identification and validation of quantitative trait loci for fertile spikelet number per spike and grain number per fertile spikelet in bread wheat (Triticum aestivum L.) - Cheng Jiang; Zhibin Xu; Xiaoli Fan; Qiang Zhou; Guangsi Ji; Liangen Chen; Qin Yu; Simin Liao; Yun Zhao; Bo Feng; Tao Wang (Theoretical and Applied Genetics, 2023)

Fabrication of high strength cold-set sodium alginate/whey protein nanofiber double network hydrogels and their interaction with curcumin - Sijie Wu; Lu Wang; Yingying Zhao; Bilian Chen; Dan Qiu; Peilong Sun; Ping Shao; Simin Feng (Food Research International, 2023)

Unsynchronized migrations of different salt ions and ice microstructure development during unidirectional freeze-thaw - Ruiqi Wang; Yaxian Hu; Xinhao Yuan; Junying Chen; Simin Jiang; Xianwen Li (Desalination, 2023)

Effect of Distinct Evaluation Objectives on Different Precipitation Downscaling Methods and the Corresponding Potential Impacts on Catchment Runoff Modelling - Xumin Zhang; Simin Qu; Jijie Shen; Yingbing Chen; Xiaoqiang Yang; Peng Jiang; Peng Shi (Water Resources Management, 2023)

Deep eutectic solvent on extraction of flavonoid glycosides from Dendrobium officinale and rapid identification with UPLC-triple-TOF/MS - Minghui Sui; Simin Feng; Gaodan Liu; Bilian Chen; Zhenhao Li; Ping Shao (Food Chemistry, 2023)

Causes of the unexpected slowness in reducing winter PM2.5 for 2014–2018 in Henan Province - Xuwu Chen; Xiaodong Li; Jie Liang; Xin Li; Shuai Li; Gaojie Chen; Zuo Chen; Simin Dai; Juan Bin; Yifan Tang (Environmental Pollution, 2023)

Spiral donor-based host materials for highly efficient blue thermally activated delayed fluorescence OLEDs - Deli Li; Mengke Li; Wei Li; Wenqi Li; Zijian Chen; Xiaomei Peng; Denghui Liu; Guo-Xi Yang; Simin Jiang; Yiyang Gan; Zhihai Yang; Kunkun Liu; et al. (Chemical Engineering Journal, 2023)

Short-term responses of phytoplankton size-fractionated structure and photosynthetic physiology to thermal effluent in a subtropical coastal bay - Simin Hu; Chen Zhang; Qingxia Liu; Tao Li; Hui Huang; Sheng Liu (Frontiers in Marine Science, 2023)
Elevated water temperature caused by the thermal discharge from power plants can exert multiple ecological impacts on the phytoplankton community in coastal ecosystems. Most recent studies have focused on the reshaping effects on the community structure; however, the short-term response of phytoplankton physiology to thermal discharge remains unclear. This study conducted research on the scope of thermal discharge from the nuclear power plant and the size-fractionated phytoplankton structure combined with photosynthetic physiology in Daya Bay, China. The thermal discharge significantly affected the surface temperature in the outlet regions, and the thermal plume mainly diffused along the northeast coast of the outfall site, resulting in a significant difference in the surface temperature between the inlet and outlet transects ( p< 0.05). Elevated surface temperatures decreased the total chlorophyll a concentrations by 33.19% at the outlet regions, with pico-phytoplankton decreasing the most. Chlorophyll a concentrations were higher at sites further away from the outlets, indicating that elevated water temperature might stimulate the rapid growth of phytoplankton, especially nano-phytoplankton which replaced pico-phytoplankton as the dominant group at stations away from the outlets. Significant negative correlations were observed between the photochemical quantum yield ( F v /F m ) and temperature ( p< 0.05), and the relative electron transport rate (rETR) and temperature ( p< 0.05). Phytoplankton showed a normal photosynthetic physiological state at most sites with a surface temperature<33°C but was severely affected at the outlet site with a 5°C rise, decreasing from ~0.5 on the inlet transect to 0.07. During the diurnal survey, the high temperatures near the outlet at midday had a compensatory effect on phytoplankton’s light suppression. The results indicated that the physiological state of phytoplankton was clearly influenced by the thermal discharge with diurnal variation, and different size-fractionated phytoplankton groups exhibited heterogeneous responses. The findings may provide further insights into the ecological impacts of thermal discharges as well as global warming in subtropical regions.

Classifying motion states of AUV based on graph representation for multivariate time series - Chen Feng; Shuang Gao; Simin Chen; Zhongke Gao; Celso Grebogi (Ocean Engineering, 2023)

Plant polysaccharide itself as hydrogen bond donor in a deep eutectic system-based mechanochemical extraction method - Min Liu; Simin Wang; Wentao Bi; David Da Yong Chen (Food Chemistry, 2023)

Planar D-σ-A type thermally activated delayed fluorescence material with Intra- and intermolecular charge transfer characteristics - Simin Jiang; Jianyin Lin; Deli Li; Mengke Li; Yanmei He; Wentao Xie; Jiting Chen; Yiyang Gan; Guo-Xi Yang; Zhihai Yang; Wei Li; Shi-Jian Su (Chemical Engineering Journal, 2023)

Genetic Diversity and Differences among Three F1 Families and Two Wild Populations of Genus Scylla Using Microsatellite Markers - Weifeng Gao; Wenxiao Cui; Fangchun Wu; Huiying Chen; Simin Liu; Mengyun Guan; Hafiz Sohaib Ahmed Saqib; Shaopan Ye; Mhd Ikhwanuddin; Hongyu Ma (Fishes, 2022)
Genetic diversity is the determinant of the allocation of germplasm resources in the genetic improvement of aquaculture species. In this study, three F1 families, including a hybrid Scylla family (S. paramamosain ♂ × S. serrata ♀), a paternal family of S. paramamosain, a maternal family of S. serrata, and two wild populations, including a paternal population of S. paramamosain and a maternal population of S. serrata, were used to investigate the genetic diversity and genetic difference. The results indicated that 98 alleles of nine microsatellites loci were observed in five Scylla populations. The highest average value of Ho (observed heterozygosity), He (expected heterozygosity), and PIC (polymorphic information content) of the wild S. paramamosain population were 0.790, 0.799, and 0.771, respectively, suggesting the wild paternal population has high genetic diversity. The comparative analysis of PIC, Fst (fixation index), and HWE (Hardy–Weinberg equilibrium) indicated that the paternal S. paramamosain may be more suitable for artificial breeding than the maternal S. serrata from the perspective of allele frequency. Analysis of molecular variance analysis (AMOVA) showed that the total genetic variation mainly occurred within populations (73.28%), demonstrating that artificial breeding may induce genetic differentiation of the family groups of Scylla. The results of the analysis of Fst value, UPGMA (unweighted pair-group mean analysis) dendrogram, and genetic diversity indicated that the F1 hybrid offspring had a close genetic distance and high genetic identity with the paternal S. paramamosain populations. It indicated that the F1 hybrid offspring showed potential paternal genetic affinities and a similar potential for artificial breeding with S. paramamosain. The study will provide valuable information to evaluate the difference in the genetic diversity and population structure between hybrid offspring and distinct parental populations of Scylla.

Assessing the total factor productivity growth decomposition: the transformation of economic growth momentum and policy choice in China - Feng Luo; Feng Chen; Dandan Yang; Simin Yang (Environmental Science and Pollution Research, 2022)

Microbial communities associated with epilithic algal matrix with different morphological characters in Luhuitou fringing reef - Tiancheng Zhou; Simin Hu; Nan Jia; Chen Zhang; Hui Huang; Sheng Liu (Frontiers in Marine Science, 2022)
The microbiota is an important component of the epilithic algal matrix (EAM) and plays a central role in the biogeochemical cycling of important nutrients in coral reef ecosystems. Insufficient studies on EAM microbiota diversity have led to a limited understanding of the ecological functions of EAMs in different states. To explore the microbial community of EAMs in the Luhuitou fringing reef in Sanya, China, which has undergone the incessant expansion and domination of algae over the past several decades, investigations were conducted in the reef’s intertidal zone. Five types of substrate habitats (dead branching coral, dead massive coral, dead flat coral, granite block, and concrete block) were selected, and their microbial communities were analyzed by high-throughput sequencing of EAM holobionts using the 16S rDNA V4 region. Proteobacteria was the most abundant group, accounting for more than 70% of reads of the microbial composition across all sites, followed by Cyanobacteria (15.89%) and Bacteroidetes (5.93%), respectively. Cluster analysis divided all microbial communities into three groups, namely short, medium, and long EAMs. Algal length was the most important morphological factor impacting the differences in the composition of the EAM microbiota. The three EAM groups had 52 common OTUs and 78.52% common sequences, among which the most abundant were Vibrio spp. and Photobacterium spp. The three types of EAM also had unique OTUs. The short EAMs had 238 unique OTUs and 48.61% unique sequences, mainly in the genera Shewanella and Cyanobacterium . The medium EAMs contained 130 unique OTUs and 4.36% unique sequences, mainly in the genera Pseudomonas and Bacillus . The long EAMs only had 27 unique OTUs and 4.13% unique sequences, mainly in the genus Marinobacter . Compared with short EAM, medium and long EAM had a lower proportion of autotrophic bacteria and higher proportion of potential pathogenic bacteria. It is suggested that EAMs with different phenotypes have different microbial compositions, and the ecological function of the EAM microbiota changes from autotrophic to pathogenic with an increase in algal length. As EAMs have expanded on coastal coral reefs worldwide, it is essential to comprehensively explore the community structure and ecological role of their microbial communities.

New insights into the mechanism of RPA in preserving genome stability - Simin Zhang; Xuejie Wang; Han Zhao; Jingyao Shi; Xuefeng Chen (Genome Instability & Disease, 2022)

Alterations in gut microbiota affect behavioral and inflammatory responses to methamphetamine in mice - Simin Lai; Jing Wang; Biao Wang; Rui Wang; Guodong Li; Yuwei Jia; Teng Chen; Yanjiong Chen (Psychopharmacology, 2022)

Effects of soil organism interactions and temperature on carbon use efficiency in three different forest soils - Simin Wang; Xiaoyun Chen; Debao Li; Jianping Wu (Soil Ecology Letters, 2021)

Paleoclimatic proxies from global closed basins and the possible beginning of Anthropocene - Yu Li; Qin Han; Lu Hao; Xinzhong Zhang; Dawei Chen; Yuxin Zhang; Lingmei Xu; Wangting Ye; Simin Peng; Yichan Li; Zhuowen Feng; Hebin Liu (Journal of Geographical Sciences, 2021)

A two-level storage strategy for map-reduce enabled computation of local map algebra - Jianbo Zhang; Simin Zhou; Tingnan Liang; Yongchang Li; Caikun Chen; Hao Xia (Earth Science Informatics, 2020)

Genome-wide identification, characterization analysis and expression profiling of auxin-responsive GH3 family genes in wheat (Triticum aestivum L.) - Wenqiang Jiang; Junliang Yin; Haotian Zhang; Yiqin He; Simin Shuai; Shuhui Chen; Sunlin Cao; Wei Li; Dongfang Ma; Huaigu Chen (Molecular Biology Reports, 2020)

Correction to: Fine mapping and identification of the fuzzless gene GaFzl in DPL972 (Gossypium arboreum) - Xiaoxu Feng; Hailiang Cheng; Dongyun Zuo; Youping Zhang; Qiaolian Wang; Ke Liu; Javaria Ashraf; Qiuhong Yang; Simin Li; Xiaoqin Chen; Guoli Song (Theoretical and Applied Genetics, 2019)

Fine mapping and identification of the fuzzless gene GaFzl in DPL972 (Gossypium arboreum) - Xiaoxu Feng; Hailiang Cheng; Dongyun Zuo; Youping Zhang; Qiaolian Wang; Ke Liu; Javaria Ashraf; Qiuhong Yang; Simin Li; Xiaoqin Chen; Guoli Song (Theoretical and Applied Genetics, 2019)

Divergent Selection of Pattern Recognition Receptors in Mammals with Different Ecological Characteristics - Ran Tian; Meixiu Chen; Simin Chai; Xinghua Rong; Bingyao Chen; Wenhua Ren; Shixia Xu; Guang Yang (Journal of Molecular Evolution, 2018)

Spatial Distribution and Temporal Trends in Precipitation Concentration Indices for the Southwest China - Peng Shi; Miao Wu; Simin Qu; Peng Jiang; Xueyuan Qiao; Xi Chen; Mi Zhou; Zhicai Zhang (Water Resources Management, 2015)

Spatial distribution and temporal trends in daily and monthly precipitation concentration indices in the upper reaches of the Huai River, China - Peng Shi; Xueyuan Qiao; Xi Chen; Mi Zhou; Simin Qu; Xinxin Ma; Zhicai Zhang (Stochastic Environmental Research and Risk Assessment, 2014)

Differences in oxygen-18 and deuterium content of throughfall and rainfall during different flood events in a small headwater watershed - Simin Qu; Minmin Zhou; Peng Shi; Han Liu; Weimin Bao; Xi Chen (Isotopes in Environmental and Health Studies, 2014)

Effects of Land-Use and Climate Change on Hydrological Processes in the Upstream of Huai River, China - Peng Shi; Xinxin Ma; Yuanbing Hou; Qiongfang Li; Zhicai Zhang; Simin Qu; Chao Chen; Tao Cai; Xiuqin Fang (Water Resources Management, 2013)

Evaluating the SWAT Model for Hydrological Modeling in the Xixian Watershed and a Comparison with the XAJ Model - Peng Shi; Chao Chen; Ragahavan Srinivasan; Xuesong Zhang; Tao Cai; Xiuqin Fang; Simin Qu; Xi Chen; Qiongfang Li (Water Resources Management, 2011)